Unidentified Neuronal Surface IgG Autoantibodies in a Case of Hashimoto's Encephalopathy - Mané-Damas, Marina; Vinke, Anita; Hoffmann, Carolin; Zong, Shenghua; Losen, Mario; Molenaar, Peter C.; Damoiseaux, Jan; Koudijs, Suzanne; Rouhl, Rob P. W.; Martinez-Martinez, Pilar (Frontiers in Immunology, 2020)
Hashimoto’s encephalopathy is an encephalitis of presumed autoimmune origin characterized by the presence of autoantibodies against thyroid proteins. We present a case of a young patient with pre-existing Hashimoto’s thyroiditis and progressive cognitive complaints, absence-like episodes, and sporadic bilateral epileptiform frontal and frontotemporal activity. No abnormalities were observed during the neurological examination and on MRI. Antibodies to thyroid peroxidase (TPO) were elevated and remained positive while the symptoms were present. Levothyroxine and methylprednisolone did not ameliorate the complaints. Subsequent treatment with high-dose intravenous immunoglobulins (IVIG) led to improved cognitive functions and to the disappearance of the absence-like-episodes. Patient’s serum, but not CSF, gave a characteristic IgG-specific hippocampal pattern in rat brain immunohistochemistry; this immunoreactivity was maintained after specific and complete depletion of TPO antibodies. Serum IgG bound to primary neurons in cell culture, likely targeting a yet unidentified neuronal surface antigen. The clinical response to IVIG suggests but does not prove, that the circulating novel autoantibodies may induce the encephalopathy. It would be of interest to investigate more patients with Hashimoto’s encephalopathy for the presence of neuronal surface autoantibodies, to define their role in the disease and their target antigen(s).